Root system architecture and shoot canopy effects drive erosion control in Napier and Vetiver grasses - Michael O. Adu; Francis Kumi; Peter B. Obour; Emmanuel Arthur; Eric Oppong Danso; Samuel Banafo; Kofi Atiah; Kwadwo K. Amoah; Paul A. Asare; Joel Asiedu; Donatus B. Angnuureng; Stephen E. Moore (Ecological Engineering, 2026)

Spatio-Temporal Analysis of Greenhouse Gases Concentration in Nigeria from 2019 to 2023 - Akinlabi Oluyemi Akintuyi; Emmanuel Omokaro Wunude; Progress Peter Akpan (Remote Sensing in Earth Systems Sciences, 2026)

Experimental and computational evaluation of Hyptis suaveolens leaf-based bait against Periplaneta americana - Babasoji Percy Omoniwa; Charles Obiora Nwonuma; Titilayo Omolara Johnson; Oluwaseun Felix Oni; Eyitayo Olugbenga Adeyemi; Emenike O. Irokanulo; Abimbola Peter Oluyori; Omolola Soji-Omoniwa; Ifunanyachi Jane-Rose Oche; Olorunleke Oludipe Emmanuel (International Journal of Tropical Insect Science, 2026)

A data-driven approach to understanding hazardous material spill infiltration: From statistical insights to a case study from a rail accident scenario - Xinyi Yang; Tanzina Afrin; Emmanuel Anu Thompson; Nita Yodo; Pan Lu; Peter Oduor (Process Safety and Environmental Protection, 2026)

Identification and functional characterization of wheat calmodulin-like proteins reveals the role of TaCML22 and TaCML40 in defense response against Fusarium graminearum infection - Daniel Bimpong; Ye Dong; Zhaolan Ma; Peter Mensah; Mawuli Korsi Amenyogbe; Yan Li; Tayachew Admas Abeje; Emily Nyangoma; Sunita Etta Ombu; Nnaemeka Emmanuel Okpala; Dongfang Ma; Zhengwu Fang (Plant Science, 2026)

Introduced or established? Convergent evidence indicates imported pine wood nematode vectors occupy gaps in native distribution - Jean-Claude Grégoire; Jean Artois; Julien Claude; Marius Gilbert; Serge Morand; Géraldine Roux; Gilles San Martin; Dimitrios Avtzis; Nick Berkvens; Jochem Bonte; Hans Casteels; Sandra Closa; et al. (Journal of Pest Science, 2026)
Monitoring regulated quarantine plant pathogens and, when relevant, their vectors is compulsory in the European Union. Local Monochamus species (Coleoptera, Cerambycidae) vector the pine wood nematode, Bursaphelenchus xylophilus , a non-native pest already established in most of Portugal. Only 29 M. galloprovincialis individuals were trapped in Belgium in ten years (2013–2022), despite a dense coverage of pheromone-baited traps, suggesting absence or a very rare local occurrence in the country. In the northern neighbouring countries, only one single established population is known in The Netherlands and one in Denmark. A species distribution model based on pheromone-trap catches (negative and positive) of M. galloprovincialis from 4,914 traps in 29 European countries between 2008 and 2019 was developed, using the overall climate conditions and the distribution of seven pine tree species as explanatory variables. The effect of spatial scale was tested with a multi-scale approach. With a 225*225 km spatial grain, the major explanatory variables were the mean diurnal temperature range and, to a lesser extent, the presence of Pinus spp. The model predicted a low probability of presence in Belgium, the Netherlands, Great Britain and north-western Germany compared to southern Europe. Genotyping allowed to conclude that at least some of the beetles caught in Belgium originated from foreign locations. All catches were located close to entry points, suggesting introduction with imported material. The small size of most of the Belgian pine stands may also explain the absence or apparently transient status, or rareness of Monochamus spp. This study thus suggests that surveys in Belgium should privilege entry points rather than local forest stands.

Enhancing timber residue value and utilization: flexural properties and joint efficiency of Khaya ivorensis logging residues finger-jointed with PVAc adhesive in green and dry states - Peter Kessels Dadzie; Emmanuel Appiah-Kubi; Michael Awotwe-Mensah; Addo Koranteng; Paul Benedict Inkum; Osei Asibey (Journal of the Indian Academy of Wood Science, 2026)

Behavioral and electrophysiological responses of fall armyworm larval parasitoid Coccygidium luteum to maize and companion plant volatiles - Emmanuel Peter; Sevgan Subramanian; Abdullahi Yusuf; Samira A. Mohamed; Baldwyn Torto; Emily A. Martin; Amanuel Tamiru (BioControl, 2026)
Companion cropping and biological control are among the best agronomic practices recommended for ecologically sustainable management of the invasive fall armyworm (FAW), Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae). Companion plants may suppress the FAW population by repelling the pest, disrupting host-plant location and recruiting biocontrol agents such as parasitoids. These interactions are primarily mediated by plant-derived volatile organic compounds (VOCs). Understanding parasitoids’ responses to VOCs emitted by companion plants enables selection of suitable cultivars to enhance biological control and design appropriate intercropping systems for effective FAW management. This study investigated behavioral and electrophysiological responses of a key FAW larval parasitoid, Coccygidium luteum Brullé (Hymenoptera: Braconidae), to odors from maize and different companion crops used in maize-based intercropping systems. In an olfactometer bioassay, gravid C. luteum were attracted to volatiles from FAW-damaged maize and intact companion plants (sweet potato, beans, groundnut) compared to control, but not to intact maize or cassava. Interestingly, females of C. luteum were equally attracted to volatiles from intact companion plants and FAW-damaged maize in multiple-treatment assays, suggesting that certain VOCs emitted by both plants may have ecological relevance. Chemical and electrophysiological analyses identified several bioactive compounds in the companion plant volatiles, including ( E )-2-hexenal, (Z)-3-hexenyl acetate, nonanal, ( E )-β-ocimene, ( E )-4,8-dimethyl-1,3,7-nonatriene, decanal, ( E )-nerolidol, and ( E , E )-4,8,12-trimethyl-1,3,7,11-tridecatetraene, known to influence parasitoid foraging. These findings provide further insight into the companion plants-FAW-parasitoid interactions and support the development of effective, economical, and environmentally friendly FAW management strategies using companion cropping and biological control.

Riding the waves: intergenerational digital storytelling to explore coastal flooding experiences - Crispin Rakibu Mbamba; Peter Dwumah; Elizabeth Koomson-Yalley; Emmanuel Temitope Adaranijo (Global Environmental Change, 2026)

Mathematical modeling of climate change impacts on stock market behavior: Evidence from Tanzania - Michael Peter; Silas Mirau; Emmanuel Sinkwembe; Christian Kasumo; Calisto Guambe (Journal of Environmental Management, 2026)

Spatiotemporal soil fertility responses to enhanced rock weathering along a hillslope catena within a temperate, agricultural watershed - Quinn C. Zacharias; Robert Rioux; Fengchao Sun; Wyatt Tatge; Evelin Pihlap; Emmanuel Nyavor; David A. Foster; Joshua L. Warren; Mark A. Bradford; Peter Raymond; Noah Planavsky; James Saiers (Nutrient Cycling in Agroecosystems, 2026)

Diagnosing scaling bottlenecks in 10 community conservation initiatives in southern and eastern Africa - Thomas Pienkowski; Matt Clark; Arundhati Jagadish; Aklei Albert; Mohanjeet Brar; Tarn Breedveld; Linda Chinangwa; Deepali Gohil; Deziderius Irumba; Ramzy Kanaan; Rose Peter Kicheleri; Phillip Kihumuro; et al. (Conservation Biology, 2026)
Scaling area‐based conservation, including initiatives led or comanaged by Indigenous Peoples and local communities, is a flagship goal of the Kunming‐Montreal Global Biodiversity Framework. Conservationists often aspire to scale initiatives, but this is rarely achieved in practice. Identifying and addressing factors that limit initiative adoption (i.e., bottlenecks) could improve scaling strategies. We used insightsfrom 84 expert surveys to identify potential risk factors and bottlenecks to scaling 10 community, area‐based initiatives in southern and eastern Africa. The number of reported potential risk factors and bottlenecks varied among initiatives. However, unfair benefit sharing, unequal decision‐making, inflexible rules, and top‐down leadership were frequently identified as bottlenecks. Although adopting initiatives had costs (e.g., increased local conflicts, reduced local access to natural resources and cropland), most experts believed these costs were offset by other benefits and thus did not constitute bottlenecks. Our results did not capture local perspectives, but they suggest scaling strategies that strengthen environmental governance may support more socially just and durable approaches to meeting area‐based conservation goals.

In silico design, drug-likeness evaluation, and binding recognition of Tanshinone I-based PARP1 inhibitors - Mwanahamis Peter Makolo; Ismail Abubakari; Marwa Emmanuel (In Silico Pharmacology, 2026)

Development of a European Equine Tetravalent Botulism Antitoxin and Novel Purified F(ab’)2 Botulinum Type A, B, E and F Antitoxin Reference Materials - Andreas Rummel; Jasmin Weisemann; Elea Paillares; Nadja Krez; Denise Bellmann; Carmen Klepka; Jana Marielle Modenbach; Adina Przykopanski; Femke Hollwedel; Julia Jokiel; Robert Alz; Simone Ladel; et al. (Toxicon, 2026)

Widespread Shrubification on European Mountain Summits - Thomas Vanneste; Harald Pauli; Stefan Dullinger; Bente J. Graae; Otar Abdaladze; José Luis Benito Alonso; Christopher Andrews; Peter Barančok; Manfred Bardy‐Durchhalter; Haben Blondeel; Pau Carnicero; Emmanuel Corcket; et al. (Global Change Biology, 2026)
Shrubs are expanding across the cold ecosystems of our planet with potentially profound consequences for their biodiversity and functioning. However, evidence is still strongly biased towards the Arctic tundra, while a large‐scale assessment of shrub expansion in alpine areas above the elevational treeline is missing so far. Here we quantified shrub cover changes over the past two decades in 576 permanent plots of 1 m 2 spread across the alpine vegetation belt of Europe's major mountain chains. Total shrub cover clearly increased in the plots with an average rate of about 2.6% per m 2 per decade (95% CI = 1.9%–3.4%), and this expansion was more pronounced for evergreen (2.0% per m 2 per decade, CI = 1.3%–2.7%) than for deciduous species (1.7% per m 2 per decade, CI = 0.9%–2.4%). The magnitude of individual species' cover shifts was positively associated with their plant height, but negatively with their leaf nitrogen content and light affinity. In sum, we show that shrub expansion is a widespread phenomenon also in the alpine zone of European mountains, with potentially far‐reaching consequences for alpine plant dynamics, soil microclimates, snow patterns, carbon cycling, food chains and livelihoods.

Optimizing particle size for enhanced aqueous extraction of phytochemicals from medicinal plants - Doris Kumadoh; Emmanuel Adase; Mary-Ann Archer; Peter Ankutse; Michael O. Kyene; Genevieve N. Yeboah (South African Journal of Botany, 2026)

Short-term effects of Greenlandic glacial rock flour on soil physical properties and maize yield - William Akortey; Eric Oppong Danso; Christiana Dietzen; William Amponsah; Emmanuel Arthur; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Daniel Amoako Darko; Selorm Yaotse Dorvlo; Edward Benjamin Sabi; Stephen Abenney-Mickson; et al. (Nutrient Cycling in Agroecosystems, 2026)
Greenlandic glacial rock flour (GRF) serves as a valuable source of silicate minerals for CO₂ uptake through enhanced weathering. Additionally, its physico-chemical properties may influence soil hydro-physical characteristics and may also have a separate effect on crop yields. This study evaluated the effects of GRF application at 50 and 100 t/ha, along with an unamended control, on soil water content at field capacity (FC), plant-available water (PAW), saturated hydraulic conductivity (K sat ), and dry aggregate stability (DAS) over 120 days. Separately, maize dry matter yield (DMY) was assessed after 40 days of growth. The experiment was conducted across four soil textures, comprising coarse-textured soils (sand and sandy loam) and fine-textured soils (sandy clay loam and clay). The 100 t/ha application had the most significant ( p < 0.05) impact on soil properties and maize yield, while the 50 t/ha rate showed intermediate but inconsistent effects. In fine-textured soils, the 100 t/ha treatment increased FC by 15% and PAW by 27% compared to the control, whereas in coarse-textured soils, FC and PAW rose by 29% and 26%, respectively. However, Ksat decreased by 47% in fine-textured soils and 34% in coarse-textured soils compared to the control. Maize DMY for the 100 t/ha rate increased by 18% in coarse-textured soils and 38% in fine-textured soils relative to the control. These findings suggest that GRF amendment improved hydro-physical properties more in coarse-textured soils but increased yield more in fine-textured soils, and may serve as a useful co-benefit of enhanced rock weathering.

Fighting fire with fire: How military actions expand environmental destruction in informal mining - Kenneth Joseph Bansah; Paul Junior Acquah; Abigail Boafo; Ebenezer Kwadwo Siabi; Lilian Owusu; Samuel Kofi Mensah; Peter Donkor; Jeffrey Emmanuel Akoto-Domey (The Extractive Industries and Society, 2025)

Influence of SMAW and GMAW on mechanical, microstructural, and corrosion properties of high-carbon steel - Ibrahim Momoh-Bello Omiogbemi; Christian Emmanuel Olatunji; Gabriel Ayomide Awopetu; Khadija Shehu Awwal; Seun Jesuloluwa; Adekunle Akanni Adeleke; Rasheed E. Abuh; Peter Pelumi Ikubanni; Prabhu Paramasivam; Emmanuel Omotosho (Next Research, 2025)

Soil structure and pH shape prokaryotic communities in lowland soils across Denmark - Anne-Cathrine Storgaard Danielsen; Charles Pesch; Cecilie Hermansen; Caitlin Margaret Singleton; Thomas Bygh Nymann Jensen; Per Halkjær Nielsen; Mogens Humlekrog Greve; Arka Rudra; Hamed Sanei; Peter Lystbæk Weber; Emmanuel Arthur; Sebastian Gutierrez; et al. (Geoderma Regional, 2025)

Long-term Rice Straw Biochar Alters Soil Pore Connectivity and Structural Anisotropy in an Acrisol - Peter Bilson Obour; Eric Oppong Danso; Michael Osei Adu; Erastus Mak-Mensah; Eric Kofi Doe; John Bright Amoah Nyasapoh; Billey Jaafar; Daniel Selorm Kpodo; Elorm Grace Ayayi; Jacqueline Naalamle Amissah; Emmanuel Arthur (Journal of Soil Science and Plant Nutrition, 2025)

Fatty acid degradation of PUFA in gut-evacuated Artemia strains - Tânia Margarida Lourenço; Emmanuel Abatih; Peter Bossier; Annelies M. Declercq (Aquaculture International, 2025)

The Fraction of Carbon in Soil Organic Matter as a National‐Scale Soil Process Indicator - Sabine Reinsch; Inma Lebron; Lis Wollesen de Jonge; Peter L. Weber; Trine Norgaard; Emmanuel Arthur; Lucas Gomes; Charles Pesch; Karyotis Konstantinos; George Zalidis; Lur Epelde; Marija Romic; et al. (Global Change Biology, 2025)
Soil organic matter (SOM) is an important component of ecosystem carbon stocks. Generally, SOM found in mineral and organo‐mineral soils can be categorised into two fractions: particulate organic matter (POM) and mineral‐associated‐organic matter (MAOM), both of which contain soil organic carbon (SOC). Understanding the relationship between SOC and SOM fractions provides insight into SOM decomposition and SOC storage potential. Here we show an intriguingly tight relationship between the fraction of SOC in SOM (denoted as ), habitat and soil physical properties, as well as SOC stored in POM and MAOM. This opens up new ways to predict spatial variations in the distribution of POC and MAOC using more widely available data as a covariate. By compiling 14 datasets and 9503 measurements from across Europe and globally we analysed across mineral and organic soils, which fell between 0.38 and 0.58, consistent with variation in carbon of major plant components. followed a habitat gradient with lowest median values in Seagrass sediments (0.36 ± 0.09) and Permafrost habitats, followed by croplands (0.47 ± 0.08) and a maximum in semi‐natural habitats (e.g., neutral, acid and calcareous grasslands) (0.56 ± 0.07), with differences between broadleaved (0.50 ± 0.087) and coniferous woodlands (0.53 ± 0.07) which were driven by overall organic matter content. The data show a tight link between vegetation carbon and the contents of SOC and SOM across various habitats, which could be used to inform agricultural soil management, improved land‐use planning (e.g., woodlands), and tracking climate‐related SOC targets.

Quantitative and health risks evaluations of trace metals in soils and cassava tubers cultivated in farms around abandoned Ishiagu mining sites, Ebonyi State, Nigeria - Obasi Uche Orji; Peter Chinedu Agu; Boniface Anthony Ale; Kingsley Nnaemeka Okah; Udu Ama Ibiam; Geraldine Ifeoma Elom; Otuomasirichi Divine Obasi; Nkiruka Nwamaka Ezeani; Emmanuel Chidiebere Orji; Francisca Chidimma Nwiziogo; Esther Ugo Alum; Patrick Maduabuchi Aja (Environmental Monitoring and Assessment, 2025)

Density perturbations in the crust indicate potential for blind magmatism beneath magma-poor rifts - Emmanuel A. Njinju; Folarin Kolawole; Estella A. Atekwana; Rasheed Ajala; Eliot A. Atekwana; D. Sarah Stamps; Rob.L. Evans; Andrew Katumwehe; Peter H. Barry; Suzan van der Lee; John Mary Kiberu; Fred Tugume; et al. (Tectonophysics, 2025)

Assessing the impact of small-scale mining activities on land use land cover and the sustainability of mining practices in Ghana: A case of the Atiwa East district - Samuel Kofi Mensah; Emmanuel Kwesi Nyantakyi; Gifty Serwaa Mensah; Ebenezer K. Siabi; Nana Osei Bonsu Ackerson; Prince Antwi-Agyei; Peter Donkor; Sarah Elikplim Siabi (Resources Policy, 2025)

Informal artisanal and small-scale mining in sub-saharan Africa: Policy evolution, sector formalization, and future trajectories - Peter Donkor; Ebenezer Kwadwo Siabi; Samuel Kofi Mensah; Kwasi Frimpong; Christopher Vuu; Emmanuel Kwesi Nyantakyi; Elikplim Sarah Siabi; Albright Boachie- Ameyaw (Resources Policy, 2025)

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

Extraction of Various Crude Oil Fractions from Water by Sorption: An Overview - Ebuka Chizitere Emenike; Joy Adetooke Adeleke; Stephen Sunday Emmanuel; Ifeoluwa Peter Oyekunle; Ozukwe Austin Eze; Chisom T. Umeh; Kingsley O. Iwuozor; Kanika Dulta; Yogesh Kumar Awasthi; Adewale George Adeniyi (Water, Air, & Soil Pollution, 2025)

The impact of climate change on road traffic crashes in Ghana - Ruth Akorli; Philip Antwi-Agyei; Patrick Davies; James Damsere-Derry; Frank Baffour-Ata; Emmanuel Nakua; Peter Donkor; Charles Mock (International Journal of Biometeorology, 2025)

Advancing NMR-based quantification in complex mixtures using fourier transform and complete reduction to amplitude frequency table - The case of sugars - Jennifer Janovick; Krish Krishnamurthy; Peter Howard; Emmanuel Hatzakis (Analytica Chimica Acta, 2025)

Whole genome sequence of Arthrobacter sp. from Iloilo City landfill soil unveils potential plastic biodegradation genes - Jasmine Velo; Christopher Marlowe Caipang; Albert Noblezada; Lorenz Inri Banabatac; Noel Peter Tan; Victor Marco Emmanuel Ferriols (Biodegradation, 2025)

Electrochemical sensor-based assessment of CO₂ and CH₄ levels in Benin City under extreme heat wave conditions in Nigeria - Peter Ndem; Osadebe Biose; Eyo Effiong; Selina Udegbe; Justina E. Ukpebor; Ikhazuagbe H. Ifijen; Emmanuel E. Ukpebor (Environmental Monitoring and Assessment, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Axial variation in the properties of Antrocaryon micraster (Aprokuma) - Emmanuel Appiah-Kubi; Michael Awotwe-Mensah; Peter Kessels Dadzie; Haruna Seidu; Edward Achiaw Owusu; Felix Boakye (Journal of the Indian Academy of Wood Science, 2025)

Air-breathing behaviour of the African catfish (Clarias gariepinus) in response to different hypoxia, hypercapnia and temperature regimes - Kwasi Adu Obirikorang; Emmanuel Albert Viala; Jesslyn Akrokoh; David Kodjo Mensah; Henry Owusu Adjei; Jedida Osei Bediako; Eliana Opoku Agyemang; Regina Edziyie; Peter Vilhelm Skov (Environmental Biology of Fishes, 2025)

Modulation of phytochemical profiles and bioactive constituents in Ananas comosus via Lactiplantibacillus-mediated fermentation - Peter Ankutse; Faith Adisa Musumba; Muhammad Bilal; Yongbin Han; Yuqing Duan; Fang Li; Isaiah Henry Ibeogu; Emmanuel Adase (Food Bioscience, 2025)

Differential Responses of the Egg-Larval Parasitoid Chelonus Bifoveolatus To Fall Armyworm-Induced and Constitutive Volatiles of Diverse Maize Genotypes - Collins O. Onjura; Emmanuel Peter; George O. Asudi; Michael M. Gicheru; Samira A. Mohamed; Toby J. A. Bruce; Amanuel Tamiru (Journal of Chemical Ecology, 2025)
The fall armyworm (FAW), Spodoptera frugiperda , is a serious invasive crop pest and threat to food security. Conventional pest control approaches using chemical pesticides can lead to adverse environmental and human health problems calling for safer alternative pest management options. Volatile organic compounds (VOCs) released by plants constitutively and in response to herbivory have been shown to enhance ecologically benign biocontrol alternatives to chemical insecticides for pest management. However, genotypic variations in VOC emissions have also been reported for plant species including maize ( Zea mays ). Hence, a better insight into the variations in odor profiles of different maize varieties and their corresponding role in recruiting pests’ natural enemies are crucial for developing a sustainable biocontrol strategy. Our present study assessed the behavioral responses of the FAW egg-larval parasitoid, Chelonus bifoveolatus (Braconidae: Hymenoptera), to constitutive and induced volatiles from different maize landraces (Jowi Red, Nyamula) and hybrids (SC Duma, DK 777) grown in Kenya and compared their volatile profiles. In a four-arm olfactometer, female parasitoid wasps were significantly attracted to FAW oviposition-induced VOCs from SC Duma and Nyamula. Chemical analysis of test plant volatiles revealed significant variation in the quantity and quality of key bioactive VOCs such as ( E )-2-hexenal, α-pinene, ( Z )-3-hexenyl acetate, ( E )-4,8-dimethyl-1,3,7-nonatriene, α-copaene, ( E) -β-farnesene and ( E , E )-4,8,12-trimethyl-1,3,7,11-tridecatetraene. Our findings provide more insights into genetic variation in VOCs emission across maize genotypes and the corresponding differences in attraction of pest natural enemies that provide indirect defense. As such, these traits could be exploited to enhance ecologically sustainable pest management strategies.

Identification of methyl 18-methylnonadecanoate and bis(2-ethyl hexyl) phthalate as potential anticancer agents in Nauclea latifolia smith through in silico molecular modeling and simulations - Mutiu A. Alabi; Raliat A. Aladodo; Marwat D. Badmus; Mumeen O. Majekodunmi; Abdulhameed O. Alli; Sesan A. Aransiola; Fatai A. Kareem; Peter A. Adeyemo; Rahmat O. Hammed; Nafisat A. Yusuf; Love J. Ahmed; Emmanuel O. Ajani (Next Research, 2025)

Land‐Use Impacts on Plant Functional Diversity Throughout Europe - Francesca Rosa; Peter M. van Bodegom; Stefanie Hellweg; Stephan Pfister; Idoia Biurrun; Steffen Boch; Milan Chytrý; Renata Ćušterevska; Michele Dalle Fratte; Gabriella Damasceno; Emmanuel Garbolino; Jonathan Lenoir; et al. (Global Ecology and Biogeography, 2025)
Aim Global biodiversity loss resulting from anthropogenic land‐use activities is a pressing concern, requiring precise assessments of impacts at large spatial extents. Existing models mainly focus on species richness and abundance, lacking insights into ecological mechanisms and species' roles in ecosystem functioning. To bridge this gap, we conducted an extensive analysis of the impact of human land use on vascular plant functional diversity across diverse land‐use classes and bioregions in Europe, comparing it to traditional metrics. Location Europe. Time Period 1992–2019. Major Taxa Studied Vascular plants. Methods Integrating extensive databases of vegetation plots with spatial data on land use and land cover, we paired plots from areas actively used and modified by humans with plots from natural habitats under similar environmental conditions. Using species occurrences and traits, in each plot we computed three complementary functional diversity metrics (functional richness, evenness and divergence), species richness and abundance. We assessed the impact of land use by comparing the metrics in the paired plots. Results Our findings revealed that, compared to natural habitats, anthropogenic land use exhibits lower functional richness and divergence but higher functional evenness across most land‐use classes and bioregions. The response of functional richness was more marked than the other two metrics and especially pronounced in croplands and urban areas and in northern bioregions. Functional richness exhibited a pattern that did not fully overlap with the trend in species richness, providing useful complementary information. Main Conclusions We provide a large‐scale precise assessment of anthropogenic land‐use impacts on functional diversity across Europe. Our findings indicate that: (i) human disturbance significantly alters plant functional diversity compared to natural habitats; (ii) this alteration goes in the direction of functional homogenisation within sites; (iii) functional diversity metrics complement traditional metrics by offering deeper insights into the ecological mechanisms in response to anthropogenic land use.

Application of bioflocculants produced by Prestia megaterium for drinking water purification - Oluwafemi Adebayo Oyewole; Asmau Mohammed Maude; Japhet Gaius Yakubu; Desire Elechi Phillip; Abideen Ajibola; Patience Emmanuel; Olabisi Peter Abioye; Olalekan David Adeniyi; Evans Chidi Egwim; Naga Raju Maddela (Bioresource Technology Reports, 2024)

Crop Mixtures Influence Fall Armyworm Infestation and Natural Enemy Abundance in Maize-based Intercropping Systems - Emmanuel Peter; Abdullahi Yusuf; Sevgan Subramanian; Kerstin Krüger; Kristina Karlsson Green; Peter Anderson; Baldwyn Torto; Amanuel Tamiru (Journal of Crop Health, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Introgression of early shoot vigour in wheat modifies root systems, increases competitiveness and provides options for integrated weed management - Pieter-Willem Hendriks; Saliya Gurusinghe; Paul A. Weston; Peter R. Ryan; Emmanuel Delhaize; Leslie A. Weston; Gregory J. Rebetzke (Plant and Soil, 2024)
Background and aims Weeds are a major biotic stressor impacting crop production. Improving the competitiveness of wheat ( Triticum aestivum L.) could provide a useful tool in integrated weed management. While wheat typically exhibits conservative early growth, early vigour has been increased through long-term recurrent selection for greater early biomass and leaf area. However, the influence of integrating such vigour into breeding lines for improving competitive ability remains to be explored. Methods In replicated controlled environment experiments, the effect of breeding early shoot vigour on root development and below-ground competitiveness was carefully examined. Physical and chemical characteristics of wheat vigour lines were assessed and compared with commercial cultivars in hydroponics and field soil experiments. Measurements included early root growth, rhizosheath size and growth responses in the presence of annual ryegrass, a major weed in wheat production. Results The vigorous lines exhibited larger leaf widths, increased cell file number, increased total root length and larger rhizosheaths compared with commercial parents. Numerous secondary metabolites with known allelopathic effects on weeds were detected in the roots and the rhizosphere, and significant allelochemical level differences observed between distilled water and soil water extract-treated plants. Although the vigour lines were significantly more competitive than the commercial cultivars against ryegrass, they produced similar levels of phytotoxic secondary metabolites. Conclusion Competition below-ground was strongly suppressive of ryegrass for the more vigorous genotypes suggesting that breeding with shoot vigour had pleiotropic effects on key root traits for below-ground wheat competitiveness.

Unveiling the potency of tetrahydropalmitine as a green anticorrosion material for 2024 aluminum alloy in acid-chloride environments - Wilfred Emori; Rita Emmanuel Odey; Paul C. Okonkwo; Demian I. Njoku; Yuzhao Yang; Peter C. Okafor; Chunru Cheng (Journal of Environmental Chemical Engineering, 2024)

Irrigation and oil palm empty fruit bunch mulch enhance eggplant growth, radiation interception and dry matter yield - John Bright Amoah Nyasapoh; Eric Oppong Danso; Daniel Selorm Kpodo; William Amponsah; Emmanuel Arthur; Edward Benjamin Sabi; Peter Bilson Obour; William Akortey; Bernard Kwabena Boadi Mensah; Grace Elorm Ayayi; Mathias Neumann Andersen (European Journal of Agronomy, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Life Cycle Assessment and Net Energy Analysis of an Integrated Hydrothermal Liquefaction-Anaerobic Digestion of Single and Mixed Beverage Waste and Sewage Sludge - Oluwayinka M. Adedeji; Emmanuel A. Aboagye; Peter Olusakin Oladoye; Sarah K. Bauer; Kauser Jahan (Chemosphere, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

A comprehensive review of recent advances in the applications and biosynthesis of oxalic acid from bio-derived substrates - Andrew Nosakhare Amenaghawon; Joshua Efosa Ayere; Ubani Oluwaseun Amune; Ifechukwude Christopher Otuya; Emmanuel Christopher Abuga; Chinedu Lewis Anyalewechi; Oseweuba Valentine Okoro; Jude A. Okolie; Peter Kayode Oyefolu; Steve Oshiokhai Eshiemogie; Blessing Esohe Osahon; Melissa Omede; et al. (Environmental Research, 2024)

Integrated geophysical and hydrogeochemical characterization of groundwater vulnerability conditions in part of Ikom-Mamfe Embayment, southeastern Nigeria - Peter O. Odong; Ebong D. Ebong; Emmanuel A. Awak; Romeo A. Ojong; Robert B. Umera (Sustainable Water Resources Management, 2024)

Geophysical methods reveal the soil architecture and subsurface stratigraphic heterogeneities across land-lake interfaces along Lake Erie - Solomon Ehosioke; Moses B. Adebayo; Vanessa L. Bailey; Roberta Bittencourt Peixoto; Efemena D. Emmanuel; Fausto Machado-Silva; Peter J. Regier; Trisha Spanbauer; Shan Pushpajom Thomas; Nicholas D. Ward; Michael N. Weintraub; Kennedy O. Doro (Journal of Soils and Sediments, 2024)
Purpose The land-lake interface is a unique zone where terrestrial and aquatic ecosystems meet, forming part of the Earth’s most geochemically and biologically active zones. The unique characteristics of this interface are yet to be properly understood due to the inherently high spatiotemporal variability of subsurface properties, which are difficult to capture with the traditional soil sampling methods. Geophysical methods offer non-invasive techniques to capture variabilities in soil properties at a high resolution across various spatiotemporal scales. Methods We combined electromagnetic induction (EMI), electrical resistivity tomography (ERT), and ground penetrating radar (GPR) with data from soil cores and in situ sensors to investigate hydrostratigraphic heterogeneities across land-lake interfaces along the western basin of Lake Erie. Results EMI revealed high spatial heterogeneities in ECa distribution across the land-lake interfaces, with higher values in the wetland and transition zones compared to the upland zone. Soil ECa maps matched soil maps from a public database with the hydric soil units delineated as high conductivity zones (ECa > 40 mS/m). ERT and GPR showed vertical variation in soil properties with clear stratigraphic boundaries, and correlation of ERT profiles with lithologs from piezometers revealed the stratigraphic units of silt–clay and till sequence down to 3.5 m depth which are consistent with the surficial geology of the study area. Conclusions These results validate the use of multiple geophysical methods for extrapolating soil properties and mapping stratigraphic structures at land-lake interfaces, thereby providing the missing information required to improve the earth system model (ESM) of coastal interfaces.

A meta-analysis of the relationship between flock size and flight initiation distance in birds - Ling-Ying Shuai; Federico Morelli; Peter Mikula; Yanina Benedetti; Michael A. Weston; Emmanuel Ncube; Tawanda Tarakini; Mario Díaz; Gábor Markó; Jukka Jokimäki; Marja-Liisa Kaisanlahti-Jokimäki; Yuan-Yuan Cao (Animal Behaviour, 2024)

Impacts of illegal Artisanal and small-scale gold mining on livelihoods in cocoa farming communities: A case of Amansie West District, Ghana - Peter Donkor; Ebenezer Kwadwo Siabi; Kwasi Frimpong; Prince Twum Frimpong; Samuel Kofi Mensah; Christopher Vuu; Elikplim Sarah Siabi; Emmanuel Kwasi Nyantakyi; Felix Agariga; Thomas Atta-Darkwa; Jacob Kofi Mensah (Resources Policy, 2024)

A conditional mutation in a wheat (Triticum aestivum L.) gene regulating root morphology - Deying Zeng; Brett Ford; Jaroslav Doležel; Miroslava Karafiátová; Mathew J. Hayden; Tina M. Rathjen; Timothy S. George; Lawrie K. Brown; Peter R. Ryan; Filomena A. Pettolino; Ulrike Mathesius; Emmanuel Delhaize (Theoretical and Applied Genetics, 2024)
Key message Characterisation and genetic mapping of a key gene defining root morphology in bread wheat. Abstract Root morphology is central to plants for the efficient uptake up of soil water and mineral nutrients. Here we describe a conditional mutant of hexaploid wheat ( Triticum aestivum L.) that when grown in soil with high Ca 2+ develops a larger rhizosheath accompanied with shorter roots than the wild type. In wheat, rhizosheath size is a reliable surrogate for root hair length and this was verified in the mutant which possessed longer root hairs than the wild type when grown in high Ca 2+ soil. We named the mutant Stumpy and showed it to be due to a single semi-dominant mutation. The short root phenotype at high Ca 2+ was due to reduced cellular elongation which might also explain the long root hair phenotype. Analysis of root cell walls showed that the polysaccharide composition of Stumpy roots is remodelled when grown at non-permissive (high) Ca 2+ concentrations. The mutation mapped to chromosome 7B and sequencing of the 7B chromosomes in both wild type and Stumpy identified a candidate gene underlying the Stumpy mutation. As part of the process to determine whether the candidate gene was causative, we identified wheat lines in a Cadenza TILLING population with large rhizosheaths but accompanied with normal root length. This finding illustrates the potential of manipulating the gene to disconnect root length from root hair length as a means of developing wheat lines with improved efficiency of nutrient and water uptake. The Stumpy mutant will be valuable for understanding the mechanisms that regulate root morphology in wheat.

Microaerobic methane-driven denitrification in a biotrickle bed – Investigating the active microbial biofilm community composition using RNA-stable isotope probing - Emmanuel O. Egbadon; Kathryn Wigley; Sunday T. Nwoba; Carlo R. Carere; Louise Weaver; Kim Baronian; Lee Burbery; Peter A. Gostomski (Chemosphere, 2024)

Predicting Earth-Vas2 parameters of coastal plain sand aquifers using artificial neural Network(s), in the Calabar region of Nigeria - Emmanuel I. Akaerue; Obialo S. Onwuka; Anthony M. George; Stephen E. Ekwok; Saad S. Alarifi; Peter Andráš; Ahmed M. Eldosouky (Journal of African Earth Sciences, 2024)

Global energy consumption of the mineral mining industry: Exploring the historical perspective and future pathways to 2060 - Emmanuel Aramendia; Paul E. Brockway; Peter G. Taylor; Jonathan Norman (Global Environmental Change, 2023)

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Air‐breathing behavior in Heterotis niloticus fingerlings: Response to changes in oxygen, temperature, and exercise regimes - Henry Owusu Adjei; Robert Yadama Laar; Prince Ofori‐Darkwah; Emmanuel Xorla Xatse; Jedida Osei Bediako; Peter Vilhelm Skov; Kwasi Adu Obirikorang (Journal of Fish Biology, 2023)
Air‐breathing in fish is believed to have arisen as an adaptation to aquatic hypoxia. Although air‐breathing has been widely studied in numerous fish species, little is known about the obligate air‐breathing African bonytongue, Heterotis niloticus . We evaluated if abiotic factors and physical activity affect air‐breathing patterns in fingerlings. The air‐breathing frequency ( f AB ) and behavioral responses of H. niloticus fingerlings were assessed in response to environmental oxygen, temperature, and exhaustion and activity in a series of experiments. The air‐breathing behavior of H. niloticus fingerlings under optimum water conditions was characterized by swift excursions lasting less than 1 s to the air–water interface to gulp air. The intervals between air‐breaths were highly variable, ranging from 3 to 259 s. Body size only slightly affected f AB , while hypoxia, hyperthermia, and exercise stress significantly increased f AB . Progressive hypoxia from 17.69 to 2.17 kPa caused a ~2.5‐fold increase in f AB . Increasing temperatures to 27 and 32°C, from a baseline temperature of 22°C, significantly increased f AB from 0.4 ± 0.2 to 1.3 ± 0.5 and 1.6 ± 0.4 breaths min −1 , respectively. Lastly, following exhaustive exercise, f AB increased up to 3‐fold. These observations suggest that H. niloticus fingerlings are very reliant on aerial oxygen, and their air‐breathing behavior is sensitive to environmental changes and activity levels.

Quantifying root-induced soil strength, measured as soil penetration resistance, from different crop plants and soil types - Francis Kumi; Peter B. Obour; Emmanuel Arthur; Stephen E. Moore; Paul A. Asare; Joel Asiedu; Donatus B. Angnuureng; Kofi Atiah; Kwadwo K. Amoah; Shadrack K. Amponsah; Selorm Y. Dorvlo; Samuel Banafo; et al. (Soil and Tillage Research, 2023)

Genetic Diversity and Population Structure of Ugandan Soybean (Glycine max L.) Germplasm Based on DArTseq - Musondolya Mathe Lukanda; Isaac Onziga Dramadri; Emmanuel Amponsah Adjei; Perpetua Arusei; Hellen Wairimu Gitonga; Peter Wasswa; Richard Edema; Mildred Ochwo Ssemakula; Phinehas Tukamuhabwa; Geoffrey Tusiime (Plant Molecular Biology Reporter, 2023)

Correction to: Assessing the effectiveness of the TaMATE1B and TaALMT1 genes to enhance the Al3+ tolerance of durum wheat (Triticum turgidum) grown under controlled conditions and in the field - Akitomo Kawasaki; Anton P. Wasson; Evangeline Kielnhofer; Peter R. Ryan; Emmanuel Delhaize (Plant and Soil, 2023)

Type I-like metalloproteinase in the venom of the West African saw-scaled carpet viper (Echis ocellatus) has anti-trypanosomal activity against African trypanosomes - Ameh Ilu; Mathias A. Chia; Thais R. Cataldi; Carlos A. Labate; Godwin U. Ebiloma; Peter O. Yusuf; Mohammed N. Shuaibu; Emmanuel O. Balogun (Toxicon, 2023)

The status and challenges of aquaculture development in Dodoma, a semi-arid region in Tanzania - Rosemary Peter Mramba; Emmanuel Jacob Kahindi (Aquaculture International, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

An observing campaign to search for meteoroids of Bennu at Earth - Peter Jenniskens; Dante S. Lauretta; Lindsey R. Koelbel; Martin C. Towner; Phil Bland; Steve Heathcote; Timothy M.C. Abbott; Emmanuel Jehin; Toni Hanke; Elise Fahl; Rynault van Wyk; Tim Cooper; et al. (Icarus, 2023)

Evidence supports the potential for climate-smart agriculture in Tanzania - Kristal Jones; Andreea Nowak; Erika Berglund; Willow Grinnell; Emmanuel Temu; Birthe Paul; Leah L.R. Renwick; Peter Steward; Todd S. Rosenstock; Anthony A. Kimaro (Global Food Security, 2023)

Defect-controlled Ar 40 diffusion-domain structure of white micas from high-resolution Ar 40 / Ar 39 crystal-mapping in slowly-cooled muscovite - Jehiel Nteme; Stéphane Scaillet; Emmanuel Gardés; Florian Duval; Peter Nabelek; Angelo Mottolese (Geochimica et Cosmochimica Acta, 2023)

Assessing the effectiveness of the TaMATE1B and TaALMT1 genes to enhance the Al3+ tolerance of durum wheat (Triticum turgidum) grown under controlled conditions and in the field - Akitomo Kawasaki; Anton P. Wasson; Evangeline Kielnhofer; Peter R. Ryan; Emmanuel Delhaize (Plant and Soil, 2022)
Purpose Durum wheat is sensitive of acid soils because it lacks effective genes for Al 3+ tolerance. Previous research showed introgression of the TaMATE1B and TaALMT1 genes individually increased the Al 3+ tolerance of durum wheat. Here we aimed to (a) combine the genes into a single durum line, (b) compare the various introgression lines and (c) establish the effectiveness of the introgressions in improving the acid soil tolerance in the field. Methods Durum wheat lines homozygous for Al 3+ -tolerant alleles of TaMATE1B and TaALMT1 were crossed to develop a line that incorporated both genes. The parental cultivar, lines with the individual genes and the line with both genes introgressed were screened for Al 3+ tolerance by hydroponic and soil cultures in a growth cabinet. The lines were also assessed for biomass production and grain yield in the field on acid soils. Results The durum wheat lines with the various Al 3+ -tolerance genes introgressed performed better based on root growth than Jandaroi, the parental cultivar, in both hydroponic and soil assays when grown in a cabinet. The various introgression lines were tolerant of acid soils compared to Jandaroi when grown in the field as assessed by shoot biomass and grain yield. Conclusion The TaALMT1 and TaMATE1B genes improve the acid soil tolerance of durum wheat with indications that combining both genes is the most effective strategy. The various lines will be valuable to breeders who wish to enhance the acid soil tolerance of durum germplasm.

Angiotensin converting enzyme inhibitors from medicinal plants: a molecular docking and dynamic simulation approach - Olumide Samuel Fadahunsi; Olubukola Sinbad Olorunnisola; Peter Ifeoluwa Adegbola; Temitayo I. Subair; Oluwabamise Emmanuel Elegbeleye (In Silico Pharmacology, 2022)

Estimation of critical fluxes, thermal stabilities and failure criteria of cellulose-based membranes and modelling of salt diffusivity during pervaporative desalination - Samuel Eshorame Sanni; Haruna Mshelia; Emeka Emmanuel Okoro; Peter Adeniyi Alaba; Babalola Aisosa Oni; Ayodeji Ayoola (Nanotechnology for Environmental Engineering, 2022)

Organic anions facilitate the mobilization of soil organic phosphorus and its subsequent lability to phosphatases - Alan E. Richardson; Timothy S. George; Maarten Hens; Emmanuel Delhaize; Peter R. Ryan; Richard J. Simpson; Peter J. Hocking (Plant and Soil, 2022)

Effect of Anthonotha macrophyla (P. Beauv) leaf extract on carrageenan-induced paw oedema, oxidative stress makers and hyperalgesia in murine models - Emmanuel Kofi Kumatia; Frederick Ayertey; Regina Appiah-Opong; Ebenezer Ofori-Attah; Peter Bolah; Stephen Antwi; Alfred Ampomah Appiah; Augustine Ocloo (Advances in Traditional Medicine, 2022)

Pollution control in Africa: the interplay between financial integration and industrialization - Ekundayo Peter Mesagan; Foluso Akinsola; Motunrayo Akinsola; Precious Muhammed Emmanuel (Environmental Science and Pollution Research, 2022)

Loss of Neuron Navigator 2 Impairs Brain and Cerebellar Development - Andrea Accogli; Shenzhao Lu; Ilaria Musante; Paolo Scudieri; Jill A. Rosenfeld; Mariasavina Severino; Simona Baldassari; Michele Iacomino; Antonella Riva; Ganna Balagura; Gianluca Piccolo; Carlo Minetti; et al. (The Cerebellum, 2022)
Cerebellar hypoplasia and dysplasia encompass a group of clinically and genetically heterogeneous disorders frequently associated with neurodevelopmental impairment. The Neuron Navigator 2 ( NAV2 ) gene (MIM: 607,026) encodes a member of the Neuron Navigator protein family, widely expressed within the central nervous system (CNS), and particularly abundant in the developing cerebellum. Evidence across different species supports a pivotal function of NAV2 in cytoskeletal dynamics and neurite outgrowth. Specifically, deficiency of Nav2 in mice leads to cerebellar hypoplasia with abnormal foliation due to impaired axonal outgrowth. However, little is known about the involvement of the NAV2 gene in human disease phenotypes. In this study, we identified a female affected with neurodevelopmental impairment and a complex brain and cardiac malformations in which clinical exome sequencing led to the identification of NAV2 biallelic truncating variants. Through protein expression analysis and cell migration assay in patient-derived fibroblasts, we provide evidence linking NAV2 deficiency to cellular migration deficits. In model organisms, the overall CNS histopathology of the Nav2 hypomorphic mouse revealed developmental anomalies including cerebellar hypoplasia and dysplasia, corpus callosum hypo-dysgenesis, and agenesis of the olfactory bulbs. Lastly, we show that the NAV2 ortholog in Drosophila , sickie ( sick ) is widely expressed in the fly brain, and sick mutants are mostly lethal with surviving escapers showing neurobehavioral phenotypes. In summary, our results unveil a novel human neurodevelopmental disorder due to genetic loss of NAV2 , highlighting a critical conserved role of the NAV2 gene in brain and cerebellar development across species.

Impact of solar heat enhanced by the use of black polypropylene sheets on the development of Callosobruchus maculatus Fabricius (Coleoptera: Chrysomelidae) eggs and germinabilty of cowpea seeds - F. A. Ajayi; E. Peter; E. Okrikata; R. A. L. Emmanuel; S. A. Dattijo; E. A Kayode (International Journal of Tropical Insect Science, 2021)
Post-harvest losses caused by Callosobruchus maculatus is a major constraint to cowpea production and the improper use of synthetic insecticides by most farmers have resulted in environmental, health hazards, and development of insecticide resistance in insects. This study evaluates the efficacy of solar heat treatment using double-layered black polypropylene sheets in suppressing the development of the cowpea bruchid eggs and the effect of the heat absorbed on the germination potential of cowpea seeds. Five pairs of 2 – 3-day old adult C. maculatus were allowed to oviposit for ten days on 50 g cowpea seeds in a glass jar in the laboratory before exposure to 24, 48, 72 and 96 h solar heat treatment regimes. Infested cowpea seeds but not exposed to solarization was set along with the treatments while uninfested cowpea seeds was also set along and used as part of the germinability test. The experiment was laid out in a completely randomized design and treatments were replicated four times. The results showed that there were no significant differences among the number of eggs laid by adult C. maculatus on the cowpea seeds before solar heat treatment. Solar heat treatment of the cowpea seed at 24 h achieved 100% egg mortality of C. maculatus thus preventing adult emergence. The effect of solarization on seed viability showed that there were no significant differences between the infested cowpea seeds exposed to different solar radiation regimes when compared to uninfested cowpea seeds – range; 74% – 99% germination. The results showed that 24 h solar heat exposure of cowpea seeds in double-layered black polypropylene sheets could be the thermal death point of C. maculatus eggs on the seeds in the study area.

Linalool inhibits the angiogenic activity of endothelial cells by downregulating intracellular ATP levels and activating TRPM8 - Vivien Becker; Xin Hui; Lisa Nalbach; Emmanuel Ampofo; Peter Lipp; Michael D. Menger; Matthias W. Laschke; Yuan Gu (Angiogenesis, 2021)
Angiogenesis crucially contributes to various diseases, such as cancer and diabetic retinopathy. Hence, anti-angiogenic therapy is considered as a powerful strategy against these diseases. Previous studies reported that the acyclic monoterpene linalool exhibits anticancer, anti-inflammatory and anti-oxidative activity. However, the effects of linalool on angiogenesis still remain elusive. Therefore, we investigated the action of (3 R )-(−)-linalool, a main enantiomer of linalool, on the angiogenic activity of human dermal microvascular endothelial cells (HDMECs) by a panel of angiogenesis assays. Non-cytotoxic doses of linalool significantly inhibited HDMEC proliferation, migration, tube formation and spheroid sprouting. Linalool also suppressed the vascular sprouting from rat aortic rings. In addition, Matrigel plugs containing linalool exhibited a significantly reduced microvessel density 7 days after implantation into BALB/c mice. Mechanistic analyses revealed that linalool promotes the phosphorylation of extracellular signal-regulated kinase (ERK), downregulates the intracellular level of adenosine triphosphate (ATP) and activates the transient receptor potential cation channel subfamily M (melastatin) member (TRPM)8 in HDMECs. Inhibition of ERK signaling, supplementation of ATP and blockade of TRPM8 significantly counteracted linalool-suppressed HDMEC spheroid sprouting. Moreover, ATP supplementation completely reversed linalool-induced ERK phosphorylation. In addition, linalool-induced ERK phosphorylation inhibited the expression of bone morphogenetic protein (BMP)-2 and linalool-induced TRPM8 activation caused the inhibition of β1 integrin/focal adhesion kinase (FAK) signaling. These findings indicate an anti-angiogenic effect of linalool, which is mediated by downregulating intracellular ATP levels and activating TRPM8.

Structural genomic variation leads to genetic differentiation in Lake Tanganyika's sardines - Julian Junker; Jessica A. Rick; Peter B. McIntyre; Ismael Kimirei; Emmanuel A. Sweke; Julieth B. Mosille; Bernhard Wehrli; Christian Dinkel; Salome Mwaiko; Ole Seehausen; Catherine E. Wagner (Molecular Ecology, 2020)
Identifying patterns in genetic structure and the genetic basis of ecological adaptation is a core goal of evolutionary biology and can inform the management and conservation of species that are vulnerable to population declines exacerbated by climate change. We used reduced‐representation genomic sequencing methods to gain a better understanding of genetic structure among and within populations of Lake Tanganyika's two sardine species, Limnothrissa miodon and Stolothrissa tanganicae . Samples of these ecologically and economically important species were collected across the length of Lake Tanganyika, as well as from nearby Lake Kivu, where L. miodon was introduced in 1959. Our results reveal differentiation within both S. tanganicae and L. miodon that is not explained by geography. Instead, this genetic differentiation is due to the presence of large sex‐specific regions in the genomes of both species, but involving different polymorphic sites in each species. Our results therefore indicate rapidly evolving XY sex determination in the two species. Additionally, we found evidence of a large chromosomal rearrangement in L. miodon , creating two homokaryotypes and one heterokaryotype. We found all karyotypes throughout Lake Tanganyika, but the frequencies vary along a north–south gradient and differ substantially in the introduced Lake Kivu population. We do not find evidence for significant isolation by distance, even over the hundreds of kilometres covered by our sampling, but we do find shallow population structure.

“Bring fishermen at the center”: the value of local knowledge for understanding fisheries resources and climate-related changes in Lake Tanganyika - Gideon Bulengela; Paul Onyango; Joan Brehm; Peter A. Staehr; Emmanuel Sweke (Environment, Development and Sustainability, 2020)

Distribution and genetic diversity of five invasive pests of Eucalyptus in sub-Saharan Africa - Mesfin Wondafrash; Bernard Slippers; Alphonsine Nambazimana; Isaac Kayumba; Samuel Nibouche; Simon van der Lingen; Birhane A. Asfaw; Herbert Jenya; Eston K. Mutitu; Idea A. Makowe; Donald Chungu; Peter Kiwuso; et al. (Biological Invasions, 2020)

Shifts in Phytoplankton Community Structure Across an Anticyclonic Eddy Revealed From High Spectral Resolution Lidar Scattering Measurements - Jennifer A. Schulien; Alice Della Penna; Peter Gaube; Alison P. Chase; Nils Haëntjens; Jason R. Graff; Johnathan W. Hair; Chris A. Hostetler; Amy Jo Scarino; Emmanuel S. Boss; Lee Karp-Boss; Michael J. Behrenfeld (Frontiers in Marine Science, 2020)

Detection of possible spillover of a novel hantavirus in a Natal mastomys from Guinea - Léonce Kouadio; Kathrin Nowak; Emmanuel Couacy-Hymann; Chantal Akoua-Koffi; Ariane Düx; Fee Zimmermann; Bernard K. Allali; Laye Kourouma; Karim Bangoura; Sophie Koendgen; Peter T. Witkowski; Detlev H. Krüger; et al. (Virus Genes, 2020)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Crop plants with improved culture and quality traits for food, feed and other uses - Fabien Nogué; Philippe Vergne; Anne-Marie Chèvre; Jean-Eric Chauvin; Oumaya Bouchabké-Coussa; Annabelle Déjardin; Elisabeth Chevreau; Laurence Hibrand-Saint Oyant; Marianne Mazier; Pierre Barret; Emmanuel Guiderdoni; Christophe Sallaud; et al. (Transgenic Research, 2019)

State-of-the-art climate modeling of extreme precipitation over Africa: analysis of CORDEX added-value over CMIP5 - Peter Gibba; Mouhamadou Bamba Sylla; Emmanuel Chilekwu Okogbue; Amadou Thierno Gaye; Michel Nikiema; Ibourahima Kebe (Theoretical and Applied Climatology, 2019)

Globally Consistent Quantitative Observations of Planktonic Ecosystems - Fabien Lombard; Emmanuel Boss; Anya M. Waite; Meike Vogt; Julia Uitz; Lars Stemmann; Heidi M. Sosik; Jan Schulz; Jean-Baptiste Romagnan; Marc Picheral; Jay Pearlman; Mark D. Ohman; et al. (Frontiers in Marine Science, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Prevalence and risk factors associated with bovine brucellosis in herds under extensive production system in southwestern Nigeria - Akwoba Joseph Ogugua; Victor Oluwatoyin Akinseye; Eniola O. Cadmus; Emmanuel A. Jolaoluwa Awosanya; Peter Ibukun Alabi; Olugbenga S. Idowu; Samson A. Akinade; Emma J. Dale; Lorraine Perrett; Andrew Taylor; Moriyon Ignocio; Simeon I. B. Cadmus (Tropical Animal Health and Production, 2018)

In-Human Robot-Assisted Retinal Vein Cannulation, A World First - Andy Gijbels; Jonas Smits; Laurent Schoevaerdts; Koen Willekens; Emmanuel B. Vander Poorten; Peter Stalmans; Dominiek Reynaerts (Annals of Biomedical Engineering, 2018)

Does the major aluminium-resistance gene in wheat, TaALMT1, also confer tolerance to alkaline soils? - Carolina M. S. Silva; Chunyan Zhang; Gustavo Habermann; Emmanuel Delhaize; Peter R. Ryan (Plant and Soil, 2018)

Knowledge, attitudes and practices towards cystic echinococcosis in livestock among selected pastoral and agro-pastoral communities in Uganda - Leonard Omadang; Martin Chamai; Emmanuel Othieno; Andrew Okwi; Francis Olaki Inangolet; Francis Ejobi; Peter Oba; Michael Ocaido (Tropical Animal Health and Production, 2018)

Handling the phosphorus paradox in agriculture and natural ecosystems: Scarcity, necessity, and burden of P - Peter Leinweber; Ulrich Bathmann; Uwe Buczko; Caroline Douhaire; Bettina Eichler-Löbermann; Emmanuel Frossard; Felix Ekardt; Helen Jarvie; Inga Krämer; Christian Kabbe; Bernd Lennartz; Per-Erik Mellander; et al. (Ambio, 2018)

Subcellular Parkinson’s Disease-Specific Alpha-Synuclein Species Show Altered Behavior in Neurodegeneration - Rashed Abdullah; Ketan S. Patil; Benjamin Rosen; Ramavati Pal; Shubhangi Prabhudesai; Sungsu Lee; Indranil Basak; Esthelle Hoedt; Peter Yang; Keith Panick; Hsin-Pin Ho; Emmanuel Chang; et al. (Molecular Neurobiology, 2017)

Pyrrolizidine alkaloids in floral honeys of tropical Ghana and health risk assessment - Emmanuel Letsyo; Gerold Jerz; Peter Winterhalter; Arne Dübecke; Werner von der Ohe; Katharina von der Ohe; Till Beuerle (Food Additives & Contaminants Part B-Surveillance, 2017)

Rotor Tracking Using Phase of Electrograms Recorded During Atrial Fibrillation - Caroline H. Roney; Chris D. Cantwell; Norman A. Qureshi; Rasheda A. Chowdhury; Emmanuel Dupont; Phang Boon Lim; Edward J. Vigmond; Jennifer H. Tweedy; Fu Siong Ng; Nicholas S. Peters (Annals of Biomedical Engineering, 2017)

Stable Isotopes Reveal Nitrogen Loading to Lake Tanganyika from Remote Shoreline Villages - Brianne Kelly; Emmanuel Mtiti; Peter B. McIntyre; Yvonne Vadeboncoeur (Environmental Management, 2017)

The rich sides of mountain summits – a pan‐European view on aspect preferences of alpine plants - Manuela Winkler; Andrea Lamprecht; Klaus Steinbauer; Karl Hülber; Jean‐Paul Theurillat; Frank Breiner; Philippe Choler; Siegrun Ertl; Alba Gutiérrez Girón; Graziano Rossi; Pascal Vittoz; Maia Akhalkatsi; et al. (Journal of Biogeography, 2016)
Aim In the alpine life zone, plant diversity is strongly determined by local topography and microclimate. We assessed the extent to which aspect and its relatedness to temperature affect plant species diversity, and the colonization and disappearance of species on alpine summits on a pan‐European scale. Location Mountain summits in Europe's alpine life zone. Methods Vascular plant species and their percentage cover were recorded in permanent plots in each cardinal direction on 123 summits in 32 regions across Europe. For a subset from 17 regions, resurvey data and 6‐year soil temperature series were available. Differences in temperature sum and Shannon index as well as species richness, colonization and disappearance of species among cardinal directions were analysed using linear mixed‐effects and generalised mixed‐effects models, respectively. Results Temperature sums were higher in east‐ and south‐facing aspects than in the north‐facing ones, while the west‐facing ones were intermediate; differences were smallest in northern Europe. The patterns of temperature sums among aspects were consistent among years. In temperate regions, thermal differences were reflected by plant diversity, whereas this relationship was weaker or absent on Mediterranean and boreal mountains. Colonization of species was positively related to temperature on Mediterranean and temperate mountains, whereas disappearance of species was not related to temperature. Main conclusions Thermal differences caused by solar radiation determine plant species diversity on temperate mountains. Advantages for plants on eastern slopes may result from the combined effects of a longer diurnal period of radiation due to convection cloud effects in the afternoon and the sheltered position against the prevailing westerly winds. In northern Europe, long summer days and low sun angles can even out differences among aspects. On Mediterranean summits, summer drought may limit species numbers on the warmer slopes. Warmer aspects support a higher number of colonization events. Hence, aspect can be a principal determinant of the pace of climate‐induced migration processes.

Household types as a tool to understand adaptive capacity: case studies from Cambodia, Lao PDR, Bangladesh and India - Liana J. Williams; Sharmin Afroz; Peter R. Brown; Lytoua Chialue; Clemens M. Grünbühel; Tanya Jakimow; Iqbal Khan; Mao Minea; V. Ratna Reddy; Silinthone Sacklokham; Emmanuel Santoyo Rio; Mak Soeun; et al. (Climate and Development, 2016)

Effect of sphingosine-1-phosphate on L-type calcium current and Ca2+ transient in rat ventricular myocytes - Emmanuel Eroume-A Egom; James S.H. Bae; Rebecca Capel; Mark Richards; Yunbo Ke; Rebabonye B. Pharithi; Vincent Maher; Peter Kruzliak; Ming Lei (Molecular and Cellular Biochemistry, 2016)

Introgression of genes from bread wheat enhances the aluminium tolerance of durum wheat - Chang Han; Peng Zhang; Peter R. Ryan; Tina M. Rathjen; ZeHong Yan; Emmanuel Delhaize (Theoretical and Applied Genetics, 2016)

Prevalence and risk factors of Echinococcus granulosus infection in dogs in Moroto and Bukedea districts in Uganda - Peter Oba; Francis Ejobi; Leonard Omadang; Martin Chamai; Andrew Livex Okwi; Emmanuel Othieno; Francis Olaki Inangolet; Michael Ocaido (Tropical Animal Health and Production, 2016)

Variation in plant diversity in mediterranean‐climate ecosystems: the role of climatic and topographical stability - Richard M. Cowling; Alastair J. Potts; Peter L. Bradshaw; Jonathan Colville; Margarita Arianoutsou; Simon Ferrier; Felix Forest; Nikolaos M. Fyllas; Stephen D. Hopper; Fernando Ojeda; Şerban Procheş; Rhian J. Smith; et al. (Journal of Biogeography, 2015)
Aim Although all five of the major mediterranean‐climate ecosystems ( MCE s) of the world are recognized as loci of high plant species diversity and endemism, they show considerable variation in regional‐scale richness. Here, we assess the role of stable Pleistocene climate and Cenozoic topography in explaining variation in regional richness of the globe's MCE s. We hypothesize that older, more climatically stable MCE s would support more species, because they have had more time for species to accumulate than MCE s that were historically subject to greater topographic upheavals and fluctuating climates. Location South‐western Africa (Cape), south‐western Australia, California, central Chile and the eastern (Greece) and western (Spain) Mediterranean Basin. Methods We estimated plant diversity for each MCE as the intercepts of species–area curves that are homogeneous in slope across all regions. We used two down‐scaled global circulation models of the Last Glacial Maximum ( LGM ) to quantify climate stability by comparing the change in the location of MCE s between the LGM and present. We quantified the Cenozoic topographic stability of each MCE by comparing contemporary topographic profiles with those present in the late Oligocene and the early Pliocene. Results The most diverse MCE s – Cape and Australia – had the highest Cenozoic environmental stability, and the least diverse – Chile and California – had the lowest stability. Main conclusions Variation in plant diversity in MCE s is likely to be a consequence not of differences in diversification rates, but rather the persistence of numerous pre‐Pliocene clades in the more stable MCE s. The extraordinary plant diversity of the Cape is a consequence of the combined effects of both mature and recent radiations, the latter associated with increased habitat heterogeneity produced by mild tectonic uplift in the Neogene.

The age of Au–Cu–Pb-bearing veins in the poly-orogenic Ubendian Belt (Tanzania): U–Th–total Pb dating of hydrothermally altered monazite - Emmanuel Owden Kazimoto; Volker Schenk; Peter Appel (Contributions to Mineralogy and Petrology, 2015)

A global alliance declaring war on cassava viruses in Africa - James Legg; Eklou Attiogbevi Somado; Ian Barker; Larry Beach; Hernan Ceballos; Willmer Cuellar; Warid Elkhoury; Dan Gerling; Jan Helsen; Clair Hershey; Andy Jarvis; Peter Kulakow; et al. (Food Security, 2014)

Novel deletion of RPL15 identified by array-comparative genomic hybridization in Diamond–Blackfan anemia - Michael Landowski; Marie-Françoise O’Donohue; Christopher Buros; Roxanne Ghazvinian; Nathalie Montel-Lehry; Adrianna Vlachos; Colin A. Sieff; Peter E. Newburger; Edyta Niewiadomska; Michal Matysiak; Bertil Glader; Eva Atsidaftos; et al. (Human Genetics, 2013)

Three-dimensional tissue cultures: current trends and beyond - Henry Page; Peter Flood; Emmanuel G. Reynaud (Cell and Tissue Research, 2013)

Plant and microbial strategies to improve the phosphorus efficiency of agriculture - Alan E. Richardson; Jonathan P. Lynch; Peter R. Ryan; Emmanuel Delhaize; F. Andrew Smith; Sally E. Smith; Paul R. Harvey; Megan H. Ryan; Erik J. Veneklaas; Hans Lambers; Astrid Oberson; Richard A. Culvenor; et al. (Plant and Soil, 2011)

Strategies and agronomic interventions to improve the phosphorus-use efficiency of farming systems - Richard J. Simpson; Astrid Oberson; Richard A. Culvenor; Megan H. Ryan; Erik J. Veneklaas; Hans Lambers; Jonathan P. Lynch; Peter R. Ryan; Emmanuel Delhaize; F. Andrew Smith; Sally E. Smith; Paul R. Harvey; et al. (Plant and Soil, 2011)

Zinc(II) modulates specifically amyloid formation and structure in model peptides - Bruno Alies; Vincent Pradines; Isabelle Llorens-Alliot; Stéphanie Sayen; Emmanuel Guillon; Christelle Hureau; Peter Faller (JBIC Journal of Biological Inorganic Chemistry, 2011)

Future Food Production as Interplay of Natural Resources, Technology, and Human Society - Jan Jansa; Emmanuel Frossard; Peter Stamp; Michael Kreuzer; Roland W. Scholz (Journal of Industrial Ecology, 2010)

Effect of lime on root growth, morphology and the rhizosheath of cereal seedlings growing in an acid soil - Rebecca E. Haling; Richard J. Simpson; Emmanuel Delhaize; Peter J. Hocking; Alan E. Richardson (Plant and Soil, 2010)

Turbulence‐plankton interactions: a new cartoon - Peter A. Jumars; John H. Trowbridge; Emmanuel Boss; Lee Karp‐Boss (Marine Ecology, 2009)
Climate change redistributes turbulence in both space and time, adding urgency to understanding of turbulence effects. Many analytic and analog models used to simulate and assess effects of turbulence on plankton rely on simple Couette flow. There shear rates are constant and spatially uniform, and hence so is vorticity. Over the last decade, however, turbulence research within fluid dynamics has focused on the structure of dissipative vortices in space and time. Vorticity gradients, finite net diffusion of vorticity and small radii of curvature of streamlines are ubiquitous features of turbulent vortices at dissipation scales but are explicitly excluded from simple, steady Couette flows. All of these flow components contribute instabilities that cause rotation of particles and so are important to simulate in future laboratory devices designed to assess effects of turbulence on nutrient uptake, particle coagulation, motility and predator‐prey encounter in the plankton. The Burgers vortex retains these signature features of turbulence and provides a simplified “cartoon” of vortex structure and dynamics that nevertheless obeys the Navier‐Stokes equations. Moreover, this idealization closely resembles many dissipative vortices observed in both the laboratory and the field as well as in direct numerical simulations of turbulence. It is simple enough to allow both simulation in numerical models and fabrication of analog devices that selectively reproduce its features. Exercise of such numerical and analog models promises additional insights into mechanisms of turbulence effects on passive trajectories and local accumulations of both living and nonliving particles, into solute exchange with living and nonliving particles and into more subtle influences on sensory processes and swimming trajectories of plankton, including demersal organisms and settling larvae in turbulent bottom boundary layers. The literature on biological consequences of vortical turbulence has focused primarily on the smallest, Kolmogorov‐scale vortices of length scale η. Theoretical dissipation spectra and direct numerical simulation, however, indicate that typical dissipative vortices with radii of 7η to 8η, peak azimuthal speeds of order 1 cm s −1 and lifetimes of order 10 s or longer (and much longer for moderate pelagic turbulence intensities) deserve new attention in studies of biological effects of turbulence.

Small intestinal motility in soluble guanylate cyclase α1 knockout mice - Ingeborg Dhaese; Gwen Vanneste; Patrick Sips; Emmanuel S. Buys; Peter Brouckaert; Romain A. Lefebvre (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Role of the soluble guanylyl cyclase α1/α2 subunits in the relaxant effect of CO and CORM-2 in murine gastric fundus - Ole De Backer; Ellen Elinck; Patrick Sips; Emmanuel Buys; Peter Brouckaert; Romain A. Lefebvre (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Analysis of TaALMT1 traces the transmission of aluminum resistance in cultivated common wheat (Triticum aestivum L.) - Harsh Raman; Peter R. Ryan; Rosy Raman; Benjamin J. Stodart; Kerong Zhang; Peter Martin; Rachel Wood; Takayuki Sasaki; Yoko Yamamoto; Michael Mackay; Diane M. Hebb; Emmanuel Delhaize (Theoretical and Applied Genetics, 2008)

High-resolution mapping of the Alp locus and identification of a candidate gene HvMATE controlling aluminium tolerance in barley (Hordeum vulgare L.) - Junping Wang; Harsh Raman; Meixue Zhou; Peter R. Ryan; Emmanuel Delhaize; Diane M. Hebb; Neil Coombes; Neville Mendham (Theoretical and Applied Genetics, 2007)

Settling Particles in Aquatic Environments: Low Reynolds Numbers - Emmanuel Boss; Lee Karp-Boss; Peter Jumars (Oceanography, 2006)

Effects of altered citrate synthase and isocitrate dehydrogenase expression on internal citrate concentrations and citrate efflux from tobacco (Nicotiana tabacum L.) roots - Emmanuel Delhaize; Peter R Ryan; Peter J Hocking; Alan E Richardson (Plant and Soil, 2003)

Strategies to isolate transporters that facilitate organic anion efflux from plant roots - Peter R. Ryan; Bei Dong; Michelle Watt; Tatsuhiko Kataoka; Emmanuel Delhaize (Plant and Soil, 2003)

Motion of dinoflagellates in a simple shear flow - Lee Karp‐Boss; Emmanuel Boss; Peter A. Jumars (Limnology and Oceanography, 2000)
Turbulence can be highly significant to dinoflagellates by affecting their swimming motion. We examined the effects of simple shear flow on swimming trajectories and orientations of two species of dinoflagellates Glenodinium foliaceum and Alexandrium catenella . In the absence of either shear or a cue that can cause directional motion, swimming orientations of both species were insignificantly different from random. Although cells of G. foliaceum maintained their random swimming orientations upon exposure to shear, swimming orientations of both single cells and chains of A. catenella were affected by shear. Magnitude of the effect increased with shear rate. Changes in decorrelation times, as a result of exposure to shear, were observed for both species, providing another indication that shear affects swimming behavior. Decorrelation times for the swimming directions of both species were of the same order as the characteristic time scale of turbulence that would produce shear rates comparable to those examined in this study. Theoretical models that assess the effects of turbulence on vertical migration of dinoflagellates and predator‐prey interactions commonly assume that swimming motion of dinoflagellates in the presence of shear flow can be described by simple superposition of the flow on the swimming motion in the absence of flow. Our results suggest that this assumption is not universally true.